Measuring The Impact of Electronic Banking Service Quality on Customer Trust: An Applied Study on Private Banks in Syria (Journal of Hama University, 2021)
This study aimed at identifying the impact of electronic banking service quality on customer Trust within private banks in Syria, it also aimed to assess both of electronic banking service quality and customer trust in the private banking sector. In order to achieve the research objectives, a questionnaire was designed consisting of field covering dimensions of an electronic banking service quality scale developed by this study, in addition to a field specific to customer trust.The study also adopts the descriptive method, where few hypotheses are developed and tested using statistical tests in the SPSS 20 package.The study results show that electronic banking service quality positively affects customer Trust in private banks. Furthermore, electronic banking service quality seems to be moderate, in the private banks, in addition, the customer trust is strong.